ANALYSIS OF THE QUALITY OF WASTEWATER FROM THE TOFU AND MEATBALL INDUSTRY BASED ON BOD, PH, COD AND TSS PARAMETERS IN THE SENDANGGUWO SUB-DISTRICT, SEMARANG CITY - Nur Taufik; Bambang Yulianto; Pertiwi Andarani (RADJA PUBLIKA, 2026)
The meatball tofu industry in Sendangguwo Village, Semarang City, is a micro, small, and medium enterprise (MSME) with unique characteristics. It operates as a meat processing unit sourcing raw tofu externally. Its intensive animal protein processing generates liquid waste with a very high organic load. This study aims to analyze the liquid waste quality based on TSS, pH, BOD, and COD parameters, evaluating compliance with recent regulations. The research employs a quantitative descriptive method with longitudinal sampling at three points: upstream (X1), waste convergence point (X2), and downstream (X3). Analyses were conducted in an accredited environmental laboratory using SNI methods. Results indicate the Sendangguwo River's water quality significantly exceeds the Class II standards of Government Regulation No. 22 of 2021. At the discharge point (X2), BOD reached 107.25 mg/L and COD 143.29 mg/L. While statistically below the emission limits for the Meat Processing Industry under Central Java Regional Regulation No. 5 of 2012, technical analysis confirms the raw effluent concentration breaches regulations before river dilution. The river's water quality is categorized as